Diaspora-Based Cultural Diplomacy and Multilevel Governance: Evidence from the 2025 Javanese Diaspora Congress - Rachmi, Ismi Fathia; Steelyana W, Evy; Witjaksono, Armanto; WawoRuntu, Ine (Eastasouth Institute, 2026)
This study examines diaspora based cultural diplomacy through the 2025 Javanese Diaspora Congress, focusing on official engagements at the Kraton Ngayogyakarta Hadiningrat and the involvement of the Governor of the Special Region of Yogyakarta. Using a qualitative case study approach, data were drawn from media coverage, official Kraton publications, public statements from the regional government, and direct observation by the authors during the diaspora visit. The findings show that the Javanese diaspora acted as non state diplomatic actors by carrying cultural identity and shared historical narratives across borders. The Governor’s participation provided institutional legitimacy and political recognition for diaspora engagement. The Kraton strengthened symbolic authority, authenticity, and trust, framing the encounter as culturally sanctioned diplomacy rather than mere ceremony. The study highlights how collaboration among diaspora communities, subnational government, and traditional authority produces a distinctive form of subnational diplomacy grounded in cultural legitimacy.